Quantifying Green Hydrogen Yields from Photovoltaic Systems in Arid Climates: Application to Ouargla, Algeria - Dernouni, Mhamed; Gadoum, Abdelatif; Douak, Mohamed (Engineering, Technology & Applied Science Research, 2026)
Algeria, particularly its southern regions such as Ouargla, offers exceptional solar energy potential, with annual Global Horizontal Irradiance (GHI) exceeding 2,000 kWh/m2. This study evaluates the technical feasibility of green hydrogen production in Ouargla using Photovoltaic (PV) energy and a simplified modeling approach based on monthly satellite-derived solar data. A standalone 1000 m2 PV system with 20% efficiency was modeled, coupled with a Proton Exchange Membrane (PEM) electrolyzer operating at 65% efficiency. Key performance indicators, including monthly PV output, hydrogen production, electrolyzer utilization, and system efficiency, were calculated using standardized assumptions. The results indicate strong seasonal variation, with hydrogen yields peaking during summer months and total annual output reaching approximately 7,864 kg. These findings are consistent with earlier experimental and modeling studies conducted in similar arid environments and confirm Ouargla’s suitability for pre-industrial green hydrogen initiatives. The study offers a replicable framework for early-stage project assessment and supports national strategies for energy diversification and low-carbon development in high-insolation regions.